2019
DOI: 10.7861/clinmedicine.19-2-177
|View full text |Cite
|
Sign up to set email alerts
|

Head injury in the elderly – an overview for the physician

Abstract: Head injury is a common cause for hospital admission and additionally 250,000 UK inpatients fall during hospital admissions annually. Head injury most commonly occurs as a result of falls from standing height in older adults. Older adults are frequently frail and multi-morbid; many have indications for anticoagulation and antiplatelet agents. The haemorrhagic complications of head injury occur in up to 16% of anticoagulated patients sustaining a head injury. These patients suffer adverse outcomes from surgery … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
(50 reference statements)
2
6
0
Order By: Relevance
“…Our results correspond to the findings of Beedham et al, who described that frail, older patients often sustain head injury when they fall and are predisposed to hemorrhagic complications because of anticoagulant use and the effects of ageing [ 23 ]. As falling itself is associated with frailty [ 24 ] and especially seniors in a poorer health state are most likely to fall and therefore may have a higher risk of intracranial bleedings [ 25 ], the use of OAC/PAI in these patients is dangerous, although it may be necessary.…”
Section: Discussionsupporting
confidence: 92%
“…Our results correspond to the findings of Beedham et al, who described that frail, older patients often sustain head injury when they fall and are predisposed to hemorrhagic complications because of anticoagulant use and the effects of ageing [ 23 ]. As falling itself is associated with frailty [ 24 ] and especially seniors in a poorer health state are most likely to fall and therefore may have a higher risk of intracranial bleedings [ 25 ], the use of OAC/PAI in these patients is dangerous, although it may be necessary.…”
Section: Discussionsupporting
confidence: 92%
“…They include that over 10% 10,12 will have acute trauma‐related findings, deterioration can be sudden and delayed, and that up to 20% in some series undergo neurosurgical intervention 10,12,17 . Most research, however, pertains to the community‐dwelling elderly, rather than to RACF residents who are both generally frailer and more prone to falls 4–6 . Our acute intracranial trauma‐related pathology rate of 6% is consistent with that for the general elderly population, but our neurosurgical intervention rate was zero.…”
Section: Discussionmentioning
confidence: 99%
“…While falls in the elderly lead to a range of injuries, 4 intracranial trauma is acknowledged to be one of the most serious contributors to morbidity and mortality 6 . Post‐fall, up to 26% of silver trauma patients have acute trauma‐related findings on CT of the brain (CTB), with over 2% requiring neurosurgical intervention 7–12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, Beedham et al described that frail, older patients often sustain head injury when they fall and are predisposed to hemorrhagic complications because of anticoagulant use and the effects of aging [ 22 ]. This is in accordance with the findings of Karibe et al, who found falling to be one of the most common reasons for traumatic brain injury, caused by degraded motoric and physiological functions [ 23 ].…”
Section: Discussionmentioning
confidence: 99%